2018
DOI: 10.3791/57730
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Functional Silica Using a Bioinspired Method

Abstract: The goal of the protocols described herein is to synthesize bioinspired silica materials, perform enzyme encapsulation therein, and partially or totally purify the same by acid elution. By combining sodium silicate with a polyfunctional bioinspired additive, silica is rapidly formed at ambient conditions upon neutralization. The effect of neutralization rate and biomolecule addition point on silica yield are investigated, and biomolecule immobilization efficiency is reported for varying addition point. In cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 14 publications
(43 citation statements)
references
References 29 publications
(37 reference statements)
4
39
0
Order By: Relevance
“…For BIS preparation, 31.82 g (0.15 moles) sodium metasilicate (Sigma‐Aldrich) was dissolved in 4650 mL deionized water, inside a 5 L Radley's reactor. [ 13 ] The solution was brought up to a mixing speed of 450 rpm, after which 5.80 g (0.025 moles) pentaethylene hexamine (PEHA) (Sigma‐Aldrich) was added to the solution. Hydrochloric acid (350 mL, 1 m ) (Sigma‐Aldrich) was added to the reaction mixture and the pH was monitored using a pH probe.…”
Section: Methodsmentioning
confidence: 99%
“…For BIS preparation, 31.82 g (0.15 moles) sodium metasilicate (Sigma‐Aldrich) was dissolved in 4650 mL deionized water, inside a 5 L Radley's reactor. [ 13 ] The solution was brought up to a mixing speed of 450 rpm, after which 5.80 g (0.025 moles) pentaethylene hexamine (PEHA) (Sigma‐Aldrich) was added to the solution. Hydrochloric acid (350 mL, 1 m ) (Sigma‐Aldrich) was added to the reaction mixture and the pH was monitored using a pH probe.…”
Section: Methodsmentioning
confidence: 99%
“…BIS was synthesized by room-temperature precipitation at pH 7 using PEHA as a bioinspired additive. 38 These and samples of IPS were acidified to change the surface charge and hence PEHA surface concentration in the case of BIS (see Supporting Information and ref ( 35 ) for details). Samples were therefore titrated to pH 7 (corresponding to as-made BIS), pH 5 (partial PEHA removal), and pH 2 (full PEHA removal).…”
Section: Resultsmentioning
confidence: 99%
“…13,14 Previous literature found that properties of bioinspired silica depended on multiple synthesis parameters such as the pH, the type of amine additive, the type of silicon precursor, the ratio of the concentrations of the silicon precursor and amine additive (Si : N), the reagent concentration ([Si]), and the reaction time, amongst others. 11 Generally, the silica yield increased from initially 0 to 100 mol% with decreasing Si : N ratio and increasing reaction time. [15][16][17] Small straight chain amines such as tetraethylenepentamine (TEPA), as well as polymeric ones such as poly(ethylene imine) (PEI) were found to produce yields of around 50 mol%.…”
Section: Introductionmentioning
confidence: 90%
“…Addition of acid then causes the monosilicic acid to condense and polymerise to form oligomers, which subsequently undergo growth and maturation to a solid silica "polymer" that precipitates. This method has been extensively reported and reviewed elsewhere; 2,6,8,10,11 below a brief summary of investigations relevant to the optimisation and modelling of this synthesis is provided.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation